THE ROLE OF BROAD BEAN AND ONOION INTERCROPPING ON PRODUCTIVITY OF BOTH CROPS AND NITROGEN BUDGET IN SOIL - & Albayati, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiment was conducted at the College of Physical Education & Sport Science-University of Baghdad /Jaderiea fields at 2015-2016 season, to study the effect of planting Broad bean and onion either in monoculture or intercropped (bicultural ) interacted with three levels of nitrogen (0,40,and 80 kg N ha-1) on growth and productivity of both crops ,amount of N taken up and on nitrogen budget in a split plot experiment within RCBD in three replicates . Nitrogen application especially 2nd level (80 kg N ha-1) significantly increased growth and yield of Broad bean . Yield of fresh pods increased from 1.36 kg plant-1 at control to 1.74 kg plant-1 with N2. Nitrogen application at 80 kg N ha-1 increased the uptake (content) of nitrogen by 245.11% compared to control. Nitrogen application especially 2nd level (80 kg N ha-1) significantly increased growth and yield of Onion. Fresh weight of onion bulbs increased from 27.3 to 37.2 and dry weight from 17.8 to 22.8 g plant-1 due to the application of the 2nd level of nitrogen. Nitrogen application at 80 kg N ha-1 increased the uptake (content) of nitrogen in onion. Planting Broad bean in monoculture gave better results than bicultural with Onion. However, yield of Broad bean was reasonable in both cultures due to the ability of Broad bean crop for competition with Onion. Monoculture of Onion gave better results than bicultural. In spite of the low production of Onion in bicultural but two crops can be gained at the same field. Results of nitrogen budget revealed that the budget was surplus with Broad bean as a result of N fixation and in shortage with Onion.